Using synthetic emission maps to constrain the structure of the Milky Way - Pettitt, Alex; Dobbs, Clare; Acreman, David; Price, Daniel (arXiv.org, 2013)
We present the current standing of an investigation into the structure of the Milky Way. We use smoothed particle hydrodynamics (SPH) to simulate the ISM gas in the Milky Way under the effect of a number of different gravitational potentials representing the spiral arms and nuclear bars, both fixed and time-dependent. The gas is subject to ISM cooling and chemistry, enabling us to track the CO and HI density. We use a 3D grid-based radiative transfer code to simulate the emission from the SPH output, allowing for the construction of synthetic longitude-velocity maps as viewed from the Earth. By comparing these maps with the observed emission in CO and HI from the Milky Way (Dame et al. 2001, Kalberla et al. 2005), we can infer the arm/bar geometry that provides a best fit to our Galaxy. By doing so we aim to answer key questions concerning the morphology of the Milky Way such as the number of the spiral arms, the pattern speeds of the bar(s) and arms, the pitch angle of the arms and shape of the bar(s)